2013
DOI: 10.1152/ajpregu.00418.2012
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle PLIN proteins, ATGL and CGI-58, interactions at rest and following stimulated contraction

Abstract: Evidence indicates that skeletal muscle lipid droplet-associated proteins (PLINs) regulate lipolysis through protein-protein interactions on the lipid droplet surface. In adipocytes, PLIN1 is thought to regulate lipolysis by directly interacting with comparative gene identification-58 (CGI-58), an activator of adipose triglyceride lipase (ATGL). Upon lipolytic stimulation, PLIN1 is phosphorylated, releasing CGI-58 to fully activate ATGL and initiate triglyceride breakdown. The absence of PLIN1 in skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 70 publications
8
99
0
Order By: Relevance
“…In isolated soleus muscle, HSL translocates to PLIN2-coated lipid droplets with either ␤-adrenergic stimulation or electrically stimulated contraction (Prats et al 2006). In addition, recent work in isolated rat soleus muscle has revealed that PLIN2 interacts with HSL, as well as with ATGL, and that this interaction is unchanged following stimulated contraction or epinephrine stimulation (MacPherson et al 2013a(MacPherson et al , 2013b. Together, this work indicates a role for PLIN2 in regulating the location of the lipases in relation to the lipid droplets.…”
Section: Plin2 As a Scaffold Proteinmentioning
confidence: 64%
See 3 more Smart Citations
“…In isolated soleus muscle, HSL translocates to PLIN2-coated lipid droplets with either ␤-adrenergic stimulation or electrically stimulated contraction (Prats et al 2006). In addition, recent work in isolated rat soleus muscle has revealed that PLIN2 interacts with HSL, as well as with ATGL, and that this interaction is unchanged following stimulated contraction or epinephrine stimulation (MacPherson et al 2013a(MacPherson et al , 2013b. Together, this work indicates a role for PLIN2 in regulating the location of the lipases in relation to the lipid droplets.…”
Section: Plin2 As a Scaffold Proteinmentioning
confidence: 64%
“…Previous work with skeletal muscle contraction has shown a translocation of HSL towards PLIN2-coated lipid droplets (Prats et al 2006). Results from recent work (MacPherson et al 2013a(MacPherson et al , 2013b provide the first evidence of a physical interaction between PLIN2 and HSL; however, this interaction remains unchanged following isolated muscle contraction or epinephrine stimulation alone or in combination. This indicates that in skeletal muscle, PLIN2 may not be involved in recruiting HSL to the lipid droplet surface, or that once HSL has translocated to the lipid droplet, it does not interact with PLIN2.…”
Section: Plin Regulation Of Hslmentioning
confidence: 91%
See 2 more Smart Citations
“…While investigation of whether exercise induces alterations in these protein-protein interactions is in its infancy, several studies are yielding exciting insight into mechanisms responsible for the exercise-induced increase in ATGL activity. [47][48][49][50][51][52][53] HSL has greater specificity for DAGs (10-fold) and cholesteryl (5-fold) than TGs or monoacylglycerides. 17 Moreover, Hsl-deficient mice exhibit DAG accrual suggesting this enzyme has a primary role in DAG hydrolysis in vivo.…”
Section: Skeletal Muscle Lipasesmentioning
confidence: 99%